Infrared thermography in children: a reliable tool for differential diagnosis of peripheral microvascular dysfunction and Raynaud’s phenomenon? - Martini, Giorgia (Pediatr Rheumatol Online J, 2019)
BACKGROUND: Infrared Thermography (IRT) has been used for over 30 years in the assessment of Raynaud Phenomenon (RP) and other peripheral microvascular dysfunctions in adults but, to date, very little experience is available on its use in children for this purpose. The first aim of the study was to assess reproducibility of thermographic examination after cold exposure by comparing inter-observer agreement in thermal imaging interpretation. The secondary aim was to evaluate whether IRT is reliable to diagnose and differentiate peripheral circulation disturbances in children. METHODS: Children with clinical diagnosis of primary Raynaud’s phenomenon (PRP), secondary RP (SRP), acrocyanosis (AC) and age-matched controls underwent sequential measurements of skin temperature at distal interphalangeal (DIP) and metacarpophalangeal (MCP) joints with IRT at baseline and for 10 min after cold challenge test. Intraclass correlation coefficient (ICC) was calculated for inter-rater reliability in IRT interpretation, then temperature variations at MCP and DIP joints and the distal-dorsal difference (DDD) were analysed. RESULTS: Fourteen PRP, 16 SRP, 14 AC and 15 controls entered the study. ICC showed excellent agreement (> 0.93) for DIPs and MCPs in 192 measures for each subject. Patients with PRP, SRP and acrocyanosis showed significantly slower recovery at MCPs (p < 0.05) and at DIPs (p < 0.001) than controls. At baseline, higher temperature at DIPs and lower at MCPs was observed in PRP compared with SRP with significantly lower DDD (p < 0.001). Differently from AC, both PRP and SRP showed gain of temperature at DIPs and less at MCPs after cold challenge. PRP but not SRP patients returned to DIPs basal temperature by the end of re-warming time. Analysis of DDD confirmed that controls and PRP, SRP and AC patients significantly differed in fingers recovery pattern (p < 0.05). CONCLUSION: IRT appears reliable and reproducible in identifying children with peripheral microvascular disturbances. Our results show that IRT examination pointed out that PRP, SRP and AC patients present significant differences in basal extremities temperature and in re-warming pattern after cold challenge therefore IRT can be suggested as an objective tool for diagnosis and monitoring of disease.